The Conspiracy of the Ninth Duke of Medina Sidonia (1641) An Aristocrat in the Crisis of the Spanish Empire - Salas Almela, Luis (Brill, 2013)
In The Conspiracy of the Ninth Duke of Medina Sidonia, Luis Salas offers a penetrating analysis of a plot to incite rebellion in the region of Andalusia in 1641. Had it succeeded, the plan could have caused the collapse of the Spanish Monarchy. Salas leaves no doubt that the conspiracy indeed occurred; he analyzes the plan in depth, its architects, its supporters - both in Andalusia and abroad - how it unraveled, and how the government of Philip IV of Spain managed to survive the most dramatic months of his tumultuous reign. Salas also delves into the consequences of the subsequent punishments, which affected Portugal, the balance of power in Andalusia, and Spain's entire colonial trade.